Autophagy-Regulating microRNAs and Cancer - Gozuacik, Devrim; Akkoc, Yunus; Ozturk, Deniz Gulfem; Kocak, Muhammed (Frontiers in Oncology, 2017)
Macroautophagy (autophagy herein) is a cellular stress response and a survival pathway that is responsible for the degradation of long-lived proteins, protein aggregates as well as damaged organelles in order to maintain cellular homeostasis. Consequently, abnormalities of autophagy is associated with a number of diseases, including Alzheimers's disease, Parkinson's disease and cancer. According to the current view, autophagy seems to serve as a tumor suppressor in the early phases of cancer formation, yet in later phases, autophagy may support and/or facilitate tumor growth, spread and contribute to treatment resistance. Therefore, autophagy is considered as a stage-dependent dual player in cancer. MicroRNAs (miRNAs) are endogenous non-coding small RNAs that negatively regulate gene expression at a post-transcriptional level. MiRNAs control several fundamental biological processes and autophagy is no exception. Furthermore, accumulating data in the literature indicate that dysregulation of miRNA expression contribute to the mechanisms of cancer formation, invasion, metastasis, and affect responses to chemotherapy or radiotherapy. Therefore, considering the importance of autophagy for cancer biology, study of autophagy regulating miRNA in cancer will allow a better understanding of malignancies and lead to the development of novel disease markers and therapeutic strategies. the potential to provide study of some of these cancer-related miRNAs were also implicated in autophagy regulation. In this review, we will focus on autophagy, microRNA and cancer connection, and discuss its implications for cancer biology and cancer treatment.